Bureaucracy in America the administrative state's challenge to constitutional government - Postell, Joseph 1979- (Studies in constitutional democracy, 2017)
"The rise of the administrative state is the most significant political development in American politics over the past century. While our Constitution separates powers into three branches, and requires that the laws are made by elected representatives in the Congress, today most policies are made by unelected officials in agencies where legislative, executive, and judicial powers are combined. This threatens constitutionalism and the rule of law. This book examines the history of administrative power in America and argues that modern administrative law has failed to protect the principles of American constitutionalism as effectively as earlier approaches to regulation and administration"--Publisher's website